2017
DOI: 10.1140/epjc/s10052-017-5046-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of topology in foliated quantum Einstein gravity

Abstract: We use a functional renormalization group equation tailored to the Arnowitt–Deser–Misner formulation of gravity to study the scale dependence of Newton’s coupling and the cosmological constant on a background spacetime with topology . The resulting beta functions possess a non-trivial renormalization group fixed point, which may provide the high-energy completion of the theory through the asymptotic safety mechanism. The fixed point is robust with respect to changing the parametrization of the metric fluctuati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 144 publications
(177 reference statements)
0
66
0
Order By: Relevance
“…For small momenta, η a;h changes sign for μ → −1. Again it can be shown that this does not happen for regulators with (38).…”
Section: B Gravity Supports Asymptotic Freedommentioning
confidence: 95%
See 1 more Smart Citation
“…For small momenta, η a;h changes sign for μ → −1. Again it can be shown that this does not happen for regulators with (38).…”
Section: B Gravity Supports Asymptotic Freedommentioning
confidence: 95%
“…For these momenta, the three-point function diagrams effectively satisfy (38), and the anomalous dimension η a;h ðp 2 Þ carries the information about the graviton contribution of the beta function of the background coupling.…”
Section: A Background Observablesmentioning
confidence: 99%
“…In the next sections, we will discuss the modifications to the mass-radius relation, maximal mass, and Buchdahl limit induced by the modified TOV equation (30).…”
Section: Quantum-improved Tov Equationmentioning
confidence: 99%
“…The effective energy density q reduces to the classical proper energy density in the limit ξ → 0, as expected. The expression (33) for the effective proper energy density affects both the continuity equation (24) and the TOV equation (30) and is the only input needed to embed the scale-dependence of the running Newton coupling into the dynamics of the system.…”
Section: Mass-radius Relation For Polytropic Quantum-improved Neutmentioning
confidence: 99%
“…As a consequence the effective average action agrees with the standard effective action in this limit, lim k→0 Γ k ≡ Γ. Finally, the framework turns out to be sufficiently flexible to probe settings where different classes of metric fluctuations are admitted by either implementing a linear split [13], an exponential split [93,94], or an ADM split [95][96][97] of the gravitational degrees of freedom. Throughout this work, we will implement a linear split, decomposing the physical metric g µν into a fixed background metricḡ µν and fluctuations h µν according to…”
Section: Jhep12(2017)121mentioning
confidence: 52%